ANALYZING NETWORKS: A STUDY OF SOCIAL MEDIA NETWORK ANALYSIS - Beatriz, Priskilla; Salim, Clement Lintanglor; Hartono, Stefhanie Angelina; Michael, Maxilianus; Surya, Nathanael (Jurnal Serina Abdimas, 2024)
This paper aims to increase students' understanding of Tarakanita 2 Pluit High School regarding the benefits, network analysis and long-term impact of social media connections. The problems identified involve students' lack of understanding of the positive and negative benefits of social media network analysis. Community education methods were chosen as the main approach to achieve this goal. This method involves a seminar activity entitled "Analyzing Networks: A Study of Social Media Network Analysis," which was held on November 15 2023, and was attended by 26 grade 11 students. The focus of this activity was to provide an in-depth understanding of the basic introductory material, characteristics, and methods of social media network analysis. The proposed solution includes three main stages: presentation of the material, practical test demonstration, and awareness of the long-term benefits of social media connections. The material presented includes information regarding the positive and negative benefits of social media network analysis, characteristics of social networks, and analytical methods used to understand relationships between individuals in cyberspace. The practical test demonstration involves student interaction in analyzing social media networks directly. Awareness of the long-term benefits of social media connections is the final focus, with the aim of changing students' mindsets regarding the long-term impact of their online activities. As a result of this activity, it is hoped that there will be an increase in digital literacy and understanding of teenagers' social media, as well as providing deeper insight into relationships between individuals in cyberspace. Thus, this paper contributes to building positive awareness of social media use among high school students.